Cancer : oxidative stress and dietary antioxidants - Preedy, Victor R. (Amsterdam ; Boston : Elsevier/AP, 2014)
Cancer: Oxidative Stress and Dietary Antioxidants bridges the trans-disciplinary divide and covers in a single volume the science of oxidative stress in cancer and then the potentially therapeutic usage of natural antioxidants in the diet or food matrix. The processes within the science of oxidative stress are described in concert with other processes such as apoptosis, cell signaling, and receptor mediated responses. This approach recognizes that diseases are often multifactorial and that oxidative stress is a single component of this
Includes bibliographical references and index
1 13
Keywords: Antioxidants -- pharmacology; Antioxidants -- therapeutic use; Neoplasms -- drug therapy; Neoplasms -- etiology; Oxygen Consumption -- physiology -- Handbooks